Pupillary Pain Index Predicts Postoperative Pain but Not the Effect of Peripheral Regional Anaesthesia in Patients Undergoing Total Hip or Total Knee Arthroplasty: An Observational Study - Evgeniya Kornilov; Lena Gehlen; Dana Yacobi; Martin Soehle; Ana Kowark; Marcus Thudium (Medicina, 2023)
Background and Objectives: The pupillary pain index (PPI) allows the evaluation of intraoperative nociception by measuring pupillary reaction after a localized electrical stimulus. It was the objective of this observational cohort study to investigate the pupillary pain index (PPI) as a method to evaluate the fascia iliaca block (FIB) or adductor canal block (ACB) sensory areas during general anaesthesia in orthopaedic patients with lower-extremity joint replacement surgery. Materials and Methods: Orthopaedic patients undergoing hip or knee arthroplasty were included. After anaesthesia induction, patients received an ultrasound-guided single-shot FIB or ACB with 30 mL and 20 mL of 0.375% ropivacaine, respectively. Anaesthesia was maintained with isoflurane or propofol/remifentanil. The first PPI measurements were performed after anaesthesia induction and before block insertion, the second at the end of surgery. Pupillometry scores were evaluated in the area of the femoral or saphenous nerve (target) and C3 dermatome (control). Primary outcomes were differences between PPIs before and after peripheral block insertion as well as the relationship between PPIs and postoperative pain scores; secondary outcomes were the relationship between PPIs and opioid requirements after surgery. Results: PPI decreased significantly from the first to the second measurement (4.17 ± 2.7 vs. 1.6 ± 1.2, p < 0.001 for target; 4.46 ± 2.7 vs. 2.17 ± 2.1, p < 0.001 for control). Control and target measurements did not show significant differences. A linear regression analysis showed that early postoperative pain scores could be predicted with intraoperative piritramide with improved prediction after adding PPI scores, PCA opioids and surgery type. Forty-eight-hour pain scores at rest and in movement were correlated with intraoperative piritramide and control PPI after the PNB in movement and with second-postoperative-day opioids and target PPI scores before block insertion, respectively. Conclusions: While the effect of an FIB and ACB could not be shown with PPI postoperative pain scores due to a large effect of opioids, perioperative PPI was shown to be associated with postoperative pain. These results suggest that preoperative PPI may be used to predict postoperative pain.